Complex plumbing systems in the near subsurface: geometries of authigenic carbonates from Dolgovskoy Mound (Black Sea) constrained by analogue experiments. - Mazzini, Adriano; Ivanov, Michael K; Nermoen, Anders; Bahr, André; Bohrmann, Gerhard; Svensen, Henrik; Planke, Sverre (PANGAEA, 2008)
Targeted sampling on the Dolgovskoy Mound (northern Shatsky Ridge) revealed the presence of spectacular laterally extensive and differently shaped authigenic carbonates. The sampling stations were selected based on sidescan sonar and profiler images that show patchy backscatter and irregular and discontinuous reflections in the near subsurface. The interpretation of acoustic data from the top part of the mound supports the seafloor observations and the sampling that revealed the presence of a complex subsurface plumbing system characterized by carbonates and gas. The crusts sampled consist of carbonate cemented layered hemipelagic sedimentary Unit 1 associated with several centimetres thick microbial mats. Three different carbonate morphologies were observed: (a) tabular slabs, (b) subsurface cavernous carbonates consisting of void chambers up to 20 cm**3 in size and (c) chimney and tubular conduits vertically oriented or forming a subhorizontal network in the subsurface. The methanogenic origin of the carbonates is established based on visual observations of fluids seepage structures, 13C depletion of the carbonates (d13C varying between -36.7 per mil and -27.4 per mil), and by thin carbonate layers present within the thick microbial mats. Laboratory experiments with a Hele–Shaw cell were conducted in order to simulate the gas seepage through contrasting grain size media present on the seafloor. Combined petrography, visual observations and sandbox simulations allowed a characterization of the dynamics and the structures of the plumbing system in the near subsurface. Based on sample observations and the experiments, three observed morphologies of authigenic carbonates are interpreted, respectively, as (a) Darcian porous flow through the finely laminated clayey/coccolith-rich layers, (b) gas accumulation chambers at sites where significant fluid escape was impeded by thicker clayey layers forming the laminated Unit1 and (c) focussed vertical fluid venting and subhorizontal migration of overpressured fluids released from (b). The Hele–Shaw cell experiments represent a promising tool for investigating shallow fluid flow pathways in marine systems.
(Table 1) Summary of sampling points described and main petrographic, morphological and geochemical characteristics
Keywords: BS346GR; Center for Marine Environmental Sciences; Comment; Dolgovskoy mound; GeoB9908-1; MARUM; Mass spectrometer Finnigan MAT DeltaXP; Professor Logachev; Sample code/label; Structure; Television-Grab; TTR-15; TVG; δ13C, carbonate; δ18O, carbonate